Intelligent systems for security informatics - Yang, Christopher C. (Intelligent systems series., 2013)
Presents the knowledge and the advances in intelligent systems. In this book, the topics include data management, data and text mining for Intelligence and Security Informatics applications, deception and intent detection, terrorist and criminal social network analysis, and public health and bio-security.